Linear Enamel Hypoplasia in Permanent Dentition of Children in the Late Archaic and the Late Prehistoric River Valley - Emily Moes; Samantha H. Blatt (Dental Anthropology Association, 2018)
Bioarchaeologists often assume that the intensification of agriculture results in an increase in physiological stress, but it is necessary to also consider duration and age of occurrence of stress events. Linear enamel hypoplasias (LEH) are indicators of such events. By analyzing LEH on the permanent anterior teeth of 40 children from prehistoric Ohio Valley, this project compares the timing and duration of stress events of foragers (4000-3000 B.P.) with those of agriculturalists (A.D. 1000-1500). A scanning electron microscope was used to create 50X photomontages of the tooth surfaces. LEH from systemic stress were recorded from these photomontages as those that concurrently match among other teeth from the same individual. Ages were calculated at which stress events occurred. The total number of perikymata within each defect furrow were used to reflect the duration of the stress events. Variables were compared between samples using Fisher's exact tests and pairwise ANOVA. Agriculturalist children endured the most stress events, although foraging children suffered the longest stress events. Variation can be attributable to cultural or nutritional change in the Ohio Valley, resulting in agriculturalist children being more frail. Results are similar to previous studies exploring transitions in physiological stress with the rise of agriculture.